Enhancing students’ comprehension of metaphoric terms in physics - Kuqali, Margarita; Plaku, Megi (Edelweiss Applied Science and Technology, 2024)
This paper aims to dwell on students’ perceptions and attitudes towards metaphoric terms and some approaches that contribute to the comprehension and acquisition of basic physics metaphoric terminology for 1st-year undergraduate engineering students. Physics English terminology comprehension and acquisition is of great importance when it comes to these students. Being the lingua franca of today, mastering the basic terminology of the respective field of interest in English is demanding for everyone who aspires to have a deep understanding of their field of interest and a prosperous career in the future. To have an effective input and output in the teaching/learning process a collaboration among professionals of STEM (science, technology, engineering, and mathematics) and ESP (English for Specific Purposes) is necessitated. Physics is fundamentally dependent on abstract notions that frequently lack tangible counterparts, such as in these metaphoric terms "tunneling effect" or "black hole". Concepts expressed through such metaphoric terms assist students to envision, conceive, and acquire the latter, but can also hinder their understanding of concepts. To conduct this research, a semi–structured questionnaire was handed to 100 students of Polytechnic University of Tirana to investigate their beliefs towards these terms and to determine different approaches that will contribute to their understanding of the above-mentioned terms. The results concluded that students face challenges in comprehending a metaphoric unknown term. Nevertheless, the results indicated that the most used and preferred approaches to learning these terms are related to the professor’s assistance with explanation, analogy with everyday experiences, and visual aids, videos mainly. This study highlights the importance of collaboration between STEM and ESP in combining the linguistic-semantic nature of terms and their practical application in the function of students’ terminology acquisition.